Magnetic resonance imaging of intramedullary spinal cord lesions: A pictorial review. Issue 5 (2nd July 2014) - Watts, Jane; Box, Georgia Alexandra; Galvin, Angela; Van Tonder, Frans; Trost, Nicholas; Sutherland, Thomas
Summary Magnetic resonance imaging (MRI) is the modality of choice for the investigation of intramedullary lesions of the spinal cord. A wide variety of conditions may result in similar imaging findings on MRI, and it is essential that the reporting radiologist have a detailed understanding of spinal cord anatomy, the pertinent imaging features of specific intramedullary lesions and the typical clinical presentation of those conditions to aid clinicians to make a prompt diagnosis. This pictorial essay discusses the clinical features and MRI appearance of a number of intramedullary conditions, which can be broadly categorised as congenital, demyelinating, vascular, neoplastic or infectious, and highlights their differentiating features.